2023
DOI: 10.1073/pnas.2216903120
|View full text |Cite
|
Sign up to set email alerts
|

KIF1A is kinetically tuned to be a superengaging motor under hindering loads

Abstract: KIF1A is a highly processive vesicle transport motor in the kinesin-3 family. Mutations in KIF1A lead to neurodegenerative diseases including hereditary spastic paraplegia. We applied optical tweezers to study the ability of KIF1A to generate and sustain force against hindering loads. We used both the three-bead assay, where force is oriented parallel to the microtubule, and the traditional single-bead assay, where force is directed along the radius of the bead, resulting in a vertical force component. The ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 67 publications
3
4
0
Order By: Relevance
“…We show that replacing KIF1A’s K-loop for loop-12 of the kinesin-3 motor, KIF14, which has only a single positively charged residue located close to the MT interface, results in a significant reduction of the run-length of the motor. This result is consistent with recent reports that show that KIF1A’s K-loop and its positively-charged residues are essential for KIF1A’s superprocessivity 74, 75 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We show that replacing KIF1A’s K-loop for loop-12 of the kinesin-3 motor, KIF14, which has only a single positively charged residue located close to the MT interface, results in a significant reduction of the run-length of the motor. This result is consistent with recent reports that show that KIF1A’s K-loop and its positively-charged residues are essential for KIF1A’s superprocessivity 74, 75 .…”
Section: Discussionsupporting
confidence: 94%
“…KIF1A, like other kinesin-3 family members, has an elongated Lys-rich loop-12 referred to as the K-loop. While it has been shown that the K-loop is important for KIF1A-MT binding [72][73][74][75] , how it interacts with MTs has not been clear as most of this loop is either disordered or not resolved in X-ray crystal structures of KIF1A and in lower resolution cryo-EM structures of KIF1A-MT complexes. Our high-resolution structures of KIF1A-MT complexes show the complete polypeptide path of the K-loop (Fig.…”
Section: Structure and Role Of The Kif1a-sepcific K-loopmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that this type of behavior does not seem to be a generic feature of all kinesins. We recently studied the forces developed by KIF1A which is a member of the kinesin 3 family and we did not find such a variable type of behavior with microtubules in the three-bead assay [27]. However, in the single-bead assay the vertical force component Fz accelerated the detachment of KIF1A from the microtubule relative to the three-bead assay, which is in agreement with what we observed for KIF5B (kinesin 1) [27].…”
Section: A Surprising Discovery: Kinesin 1 and Microtubules Can Exhib...supporting
confidence: 89%
“…We recently studied the forces developed by KIF1A which is a member of the kinesin 3 family and we did not find such a variable type of behavior with microtubules in the three-bead assay [27]. However, in the single-bead assay the vertical force component Fz accelerated the detachment of KIF1A from the microtubule relative to the three-bead assay, which is in agreement with what we observed for KIF5B (kinesin 1) [27]. Since, as mentioned previously, the pair of opposing forces on the microtubule in the three-bead assay may apply in general along different protofilaments, the azimuthal angle  (cylindrical coordinates of the microtubule structure) between this pair of forces will be variable between different dumbbells (Fig.…”
Section: A Surprising Discovery: Kinesin 1 and Microtubules Can Exhib...mentioning
confidence: 91%